A Novel Human Systemic Lupus Erythematosus Model in Humanised Mice. Issue 1 (December 2017) - Gunawan, Merry; Her, Zhisheng; Liu, Min; Tan, Sue; Chan, Xue; Tan, Wilson; Dharmaraaja, Shubasree; Fan, Yong; Ong, Chee; Loh, Eva; Chang, Kenneth; Tan, Thiam; et al.
Abstract Mouse models have contributed to the bulk of knowledge on Systemic Lupus Erythematosus (SLE). Nevertheless, substantial differences exist between human and mouse immune system. We aimed to establish and characterise a SLE model mediated by human immune system. Injection of pristane into immunodeficient mice reconstituted with human immune system (humanised mice) recapitulated key SLE features, including: production of human anti-nuclear autoantibodies, lupus nephritis, and pulmonary serositis. There was a reduction in the number of human lymphocytes in peripheral blood, resembling lymphopenia in SLE patients. Concurrently, B cells and T cells were systemically hyperactivated, with a relative expansion of CD27+ and CD27− IgD− memory B cells, increased number of plasmablasts/plasma cells, and accumulation of effector memory T cells. There was also an increased production of human pro-inflammatory cytokines, including: IFN-γ, IL-8, IL-18, MCP-1, and IL-6, suggesting their role in SLE pathogenesis. Increased expression of type I IFN signature genes was also found in human hepatocytes. Altogether, we showed an SLE model that was mediated by human immune system, and which recapitulated key clinical and immunological SLE features. The advancements of humanised mice SLE model would provide anin vivo platform to facilitate translational studies and pre-clinical evaluations of human-specific mechanisms and immunotherapies.